Investigating the impact of MpAPr1, an aspartic protease from the yeast Metschnikowia pulcherrima, on wine properties - Theron, Louwrens Wiid (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.